Changes to Workflow and Process Measures in the PICU During Transition From Semi to Full Electronic Health Record. Issue 8 (October 2015) - Salib, Mina; Hoffmann, Raymond G.; Dasgupta, Mahua; Zimmerman, Haydee; Hanson, Sheila
<x xml:space="preserve">Abstract</x> Objectives: Studies showing the changes in workflow during transition from semi to full electronic medical records are lacking. This objective study is to identify the changes in workflow in the PICU during transition from semi to full electronic health record. Design: Prospective observational study. Children's Hospital of Wisconsin Institutional Review Board waived the need for approval so this study was institutional review board exempt. This study measured clinical workflow variables at a 72-bed PICU during different phases of transition to a full electronic health record, which occurred on November 4, 2012. Phases of electronic health record transition were defined as follows: pre–electronic health record (baseline data prior to transition to full electronic health record), transition phase (3 wk after electronic health record), and stabilization (6 mo after electronic health record). Data were analyzed for the three phases using Mann-Whitney U test with a two-sided p value of less than 0.05 considered significant. Setting: Seventy-two bed PICU. Patients: All patients in the PICU were included during the study periods. Measurements and Main Results: Five hundred and sixty-four patients with 2, 355 patient days were evaluated in the three phases. Duration of rounds decreased from a median of 9 minutes per patient pre–electronic health record to 7 minutes per patient post electronic health record. Time to final note decreased from 2.06 days pre–electronic health record to 0.5 days post electronic health record. Time to first medication administration after admission also decreased from 33 minutes pre–electronic health record and 7 minutes post electronic health record. Time to medication reconciliation completion was significantly higher pre–electronic health record than post electronic health record and percent of medication reconciliation completion was significantly higher pre–electronic health record than. There was no significant change in time between placement of discharge order and physical transfer from the unit. Conclusions: Transition from partial to full electronic health record significantly changes clinical workflow in a PICU with decreased duration of rounds, time to final note, time to medication administration, and time to medication reconciliation completion. There was no change in the duration from medical to physical transfer.